Aproveitamento de filer de pedreiras da região metropolitana de Goiânia em pavimentos flexíveis urbanos [manuscrito]: avaliação técnica e sócio-ambiental - LUZ, Marta Pereira da (2008)
The generation of industrial waste has been the object of increasing attention in the field of Science and Technology because of the problems which arise when it is stored and inadequately disposed of. This can have negative consequences for the worker, the company and for the neighboring population. In addition it can generate liabilities for the environment. Measures which internalize such liabilities for the productive system are necessary, but not sufficient to bring about large scale changes in what concerns the sustainable management of solid waste. Therefore, there is an urgent need for technical and participative solutions. Technical solutions would make it viable to reuse or reduce the generation of waste, while participative solutions would reduce the negative consequences for communities and bodies who directly or indirectly are part of this process. In this context, waste from the quarrying of crushed stone was studied in the metropolitan Region of Goiânia. Quarrying is an important source of resources for the economic development of the region but it is also a great generator of solid waste. The research began with the physical and chemical characterization of filler, which forms the greatest volume of solid waste, resulting from quarrying and focused on its general effects on health. It also evaluated how the workers in these companies relate to the environmental issue in this context in which they live. A survey with questions was distributed and from the answers it could be concluded that the profile of these workers is extremely lacking in information which would provide them with information to deal with legal aspects directly related to their activity. Furthermore, it could be seen that specific methodologies in Environmental Education are needed to attend to these cases. It was also detected that the accumulation of filler can be harmful to society in terms of health. This is because of its physical and chemical characteristics, and in particular its considerable concentration of silica. These facts justify the need to find a technical solution to reduce the quantity of this waste. Hence it was decided to test different blends of natural soil and filler, using laboratory tests based on soil mechanics, with a view to investigating the possibility of using filler in road pavement, as it absorbs enormous quantities of material in its constituent layers and has attracted the attention of researchers in an effort to find new alternative uses for the different types of industrial waste. At this phase, tests were carried out for characterization, CBR, dynamic triaxial tests, permeability, compressive strength using varied quantities of lateritic clay soil as filler. From the results of these tests it was possible to claim that proportions of 30% filler added to compacted soil with modified energy and 20% filler added to compacted soil with intermediate energy can be used for base and sub base purposes, respectively, in flexible urban pavements with light traffic. The result of the resilience module points to the need for prudence in the use of filler, as repeated loads of filler in the test showed that the samples which were most appropriate in the CBR Statistical Test can undergo processes leading to a loss of mechanical resistance. After deciding in the laboratory on the most appropriate proportions of soil-filler for use in pavements, an experimental track was built using this material. An analysis of its behavior was done using the following field tests: sand flagon test, speedy, dynamic cone penetration, loading plate and Benkelman beam. The results of these tests were compared with those obtained from a track built in the same location with soil-crushed rock and lateritic gravel, both considered conventional material. It could be concluded that the mechanical behavior of the experimental track built with soil-filler blends are adequate for the conditions established by the technical norm in force up until the moment they were monitored, since its mechanical behavior is comparable to that obtained when using conventional materials